Application of Problem Based Learning Models to Improve Magnetic Materials Learning Results - Shahab, Anisa Dwi Inayati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the learning outcomes of Magnetics subject in elementary schools in grade VI by applying the Problem Based Learning (PBL) learning model. The research conducted was a Classroom Action Research (PTK) in three cycles, with each cycle consisting of 1 meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is held an evaluation to determine the progress of learning outcomes. In cycle 1, students who completed after the evaluation were 51.61%. In cycle 2, students who completed after evaluation were 74.20%. In cycle 3, students who completed after the evaluation were 90.32%. These results indicate that the Problem Based Learning (PBL) learning model can improve student learning outcomes, especially science muple class VI magnetic materials at SDN 1 Jambukulon.